Enslavement and Freedom of Choice: The Perspective of the Solution-Focused Approach in the Resocialization of Addicted Youths - Szczepkowski, Jacek (Studia Paedagogica Ignatiana, 2020)
One of the manifestations of the social changes observed over the last decades is the increase in the availability of moodchanging substances and the tendency of young people to use them. This phenomenon is inseparable from a specific lifestyle and often results in exceeding social norms and breaking the law. Therefore, the current challenge is to seek effective opportunities to help addicts. As far as youth is concerned, the dimension of institutional rehabilitation, ensuring temporary isolation from the social context related to the current lifestyle, becomes particularly important. This article presents an understanding of the phenomenon of addiction from the perspective of a solution-focused approach according to the concept of the Belgian psychiatrist Luc Isebaert, co-author of the Bruges Model. Moreover, it presents institutional solutions tested in clinical conditions at the 24-hour Youth Addiction Treatment Clinic in Toruń, based on the idea of free choice. Free choice, taking into account the trap of addiction, can be treated as a desired outcome of rehabilitation effects, as well as a means leading to it. The key to responsibility remains independence, which we create by building subjectivity and freedom of choice.